FACTORS PREDICTING THE SELF CARE BEHAVIORS OF MUSLIM ELDERLY IN NAKHON SI THAMMARAT PROVINCE - Karakhuean, Naranuch; Songlead, Dolpaphat; junwin, Boonprajuk (Journal of Buddhist Anthropology, 2022)
The objectives of this research article were to 1) study the factors influencing self-care behaviors of the Muslim elderly, and 2) be able to predict self-care behaviors of the Muslim elderly in Nakhon Si Thammarat province based on personal factors, psychological factors, and social factors. This is a quantitative study in which the subjects consisted of 185 elderly Muslim people, who are 60 years old or older and live in Mueang Nakhon Si Thammarat District. A multistage randomization method was used based on the proportion of the population classified by villages and the information was collected by questionnaires. The instruments used include 1) questionnaires of personal data 2) questionnaires of self-care behaviors 3) questionnaires of elderly psychological factors 4) questionnaires of Social Factors. The content validity index of the questionnaire was 0.97, and a reliability test for Cronbach’s alpha coefficient was 0.867. Data were analyzed using percentage, mean, standard deviation, and multiple regression analysis (Stepwise Multiple Regression Analysis) based on the importance of the input variables to the equation. The study’s findings revealed that: 1) factors influencing self-care behaviors of the Muslim Elderly: psychological factors such as attitude, self-efficacy, and social factors in support of self-health care from family and health care support from all staff had a significant effect on elderly people’s self-care behaviors at a high level. 2) Predicting self-care behaviors necessitates a secondary school education or higher, monthly income, extended family traits, positive attitudes toward self-care, and internal-external beliefs about self-care. We were able to predict the self-care behaviors of Muslim elderly people in Nakhon Si Thammarat Province by 75.6%, with a statistical significance of 0.05.